Medically important bacteria isolated from commercial herbal medicines in Kampala city indicate the need to enhance safety frameworks - Walusansa, Abdul; Nakavuma, Jesca L.; Asiimwe, Savina; Ssenku, Jamilu E.; Aruhomukama, Dickson; Sekulima, Tahalu; Kafeero, Hussein M.; Anywar, Godwin; Katuura, Esther; Nabatanzi, Alice; Musisi, Nathan L.; Tugume, Arthur K. (Scientific Reports, 2022)
The high global bacterial infection burden has created need to investigate the neglected potential drivers of pathogenic bacteria, to inform disease prevention. Kampala is facing a proliferation of herbalists, selling herbal medicine (HM), of largely unregulated microbiological quality. We evaluated the bacterial contamination burden in HM sold in Kampala, to support evidence-based redress. The total viable loads (TVL), total coliform counts (TCC), E. coli counts, and prevalence of selected bacterial strains in 140 HM were examined using conventional culture, following the guidelines of World Health Organization (WHO), and Uganda National Drug Authority (NDA). Data were analyzed using D’Agostino-Pearson test, frequencies, proportions, Chi-square, and Mann–Whitney U test with STATA version-15.0. Fifty (35.7%), fifty-nine (42.1%), and twelve (8.6%) HM were unsafe for human use because they exceeded WHO’s permissible limits for TVL, TCC, and E. coli counts respectively. Solids had significantly higher mean TVL than liquids. Violation of NDA’s guidelines was significantly associated with high TVL. Fifty-nine bacteria, viz., Klebsiella pneumoniae (n = 34; 57.6%), Escherichia. coli (12; 20.3%), Staphylococcus aureus (7; 11.9%), Klebsiella oxytoca (3; 5.1%), Bacillus cereus, Pseudomonas aeruginosa, and Enterobacter spp. (1; 1.7% each), were isolated from 45 (32.1%) samples. These bacteria can cause severe clinical diseases, and promote deterioration of HM potency.
Keywords: Herbal medicine; Traditional Medical Practitioners; World Health Organization; Kampala Capital City Authority